The Effectiveness of Environmentally Friendly Business Strategies: Implementing SDGs-12 in Building the Economy in Central Lombok Regency - Nuruddin Nuruddin; Wawan Andriawan; Deva Nabilah; Andina Rahayu Putri (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This study aims to analyze the effectiveness of implementing Sustainable Development Goal (SDG) 12 on responsible consumption and production in supporting economic development in Central Lombok Regency. The current achievement of SDG 12 in the region shows disparities when compared to national progress, despite strong efforts by the central government to strengthen comprehensive environmental governance policies. Various national and regional regulations have been established, including West Nusa Tenggara Provincial Regulation No. 5 of 2019 on Waste Management. However, local performance remains limited, indicating the need for more targeted and collaborative strategies. Method: This research employs a qualitative approach through case studies and literature reviews, combining observational data, interviews, documentation, and policy analysis. The study examines the involvement of government, communities, self-help groups, and the private sector in waste management and the development of sustainability-based economic initiatives. Result: Findings reveal that waste management infrastructure and community participation remain inadequate, while policy implementation is not yet integrated across the entire value chain. Consequently, the effectiveness of SDG 12 implementation is still suboptimal, particularly in key local economic sectors such as agriculture, tourism, and recycling-based industries. The results indicate that the successful implementation of SDG 12 in Central Lombok requires multisectoral synergy through collaborative environmentally friendly business strategies. Active community engagement through waste banks, consistent regulatory support, and the adoption of circular economy models constitute essential factors in strengthening sustainable economic development. Conclusion: The study concludes that accelerating SDG 12 achievements can only be realized through integrated policies, enhanced public awareness, and adequate infrastructure provision, thereby generating balanced economic, social, and environmental impacts.